School students’ perception on risky behavior and their utilization of health care services - Che Hasan, Muhammad Kamil; Tutasting@Rawi, Noor Faizah; Nurumal, Mohd. Said; Abdul Hamid, Siti Hazariah (Faculty of Nursing of Universitas Indonesia, 2021)
The Malaysia Ministry of Health reported adolescents’ low utilization of healthcare services, although they need this service as a consequence of their involvement in risky behavior. This cross-sectional study aimed to determine adolescents’ perception on risk taking behavior and their utilization of health care services. A modified self-administered questionnaire was used to collect data from 250 secondary school students aged 13 and 14 years in one of the selected schools in Malacca, Malaysia. Data were analyzed using SPSS 20. Fastfood consumption, loitering after school, physical fighting, smoking, and non-use of helmets were the most reported risky behaviors among adolescents in Malaysia. More than half of the adolescents who knew about health care services had a positive perception on their utilization of such services. Thus, the promotion of adolescents’ health services helps increase their use of these services and consequently achieve a healthy lifestyle.